UV-Licht-induzierter Hautkrebs als neue Berufskrankheit - Diepgen, Thomas L. (Der Hautarzt, 2015)
With the revision of the German Ordinance on Occupational Diseases, skin cancer due to UV irradiation was amended as a new occupational disease to the list of occupational diseases in Germany. The new occupational disease BK 5103 has the following wording: “Squamous cell carcinoma or multiple actinic keratosis of the skin caused by natural UV irradiation”. Actinic keratoses are to be considered as multiple according to this new occupational diseases if they occur as single lesions of more than five annually, or are confluent in an area > 4 cm2 (field cancerization). It is estimated that more than 2.5 million employees are exposed to natural UV irradiation due to their work (outdoor workers) in Germany and therefore have an increased risk of skin cancer. In this article the medical and technical prerequisites which have to be fulfilled for this new occupational disease in Germany are introduced.